Complete genome sequence of Aminobacterium colombiense type strain (ALA-1T). Issue 3 (May 2010) - Chertkov, Olga; Sikorski, Johannes; Brambilla, Evelyne; Lapidus, Alla; Copeland, Alex; Glavina Del Rio, Tijana; Nolan, Matt; Lucas, Susan; Tice, Hope; Cheng, Jan-Fang; Han, Cliff; Detter, John; et al.
Abstract Aminobacterium colombiense Baenaet al. 1999 is the type species of the genusAminobacterium . This genus is of large interest because of its isolated phylogenetic location in the familySynergistaceae, its strictly anaerobic lifestyle, and its ability to grow by fermentation of a limited range of amino acids but not carbohydrates. Here we describe the features of this organism, together with the complete genome sequence and annotation. This is the second completed genome sequence of a member of the familySynergistaceae and the first genome sequence of a member of the genusAminobacterium . The 1, 980, 592 bp long genome with its 1, 914 protein-coding and 56 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project.